الذكاء الروحي لدى طلبة كلية عجلون الجامعية في ضوء بعض المتغيرات - الربضي، وائل منور سلامة Alrabadi, Wael Munawwar Salamah; المومني، فخري فلاح العلي Almoumani, Fakhri Falah Alali; فريحات، أيمن محمد أحمد (جامعة الإسكندرية - كلية رياض الأطفال, 2018)
أن مستوى الذكاء الروحي لدى أفراد عينة الدراسة على المقياس بصورته الكلية جاء بدرجة متوسطة هدفت الدراسة إلى تعرف مستوى الذكاء الروحي لدى عينة من طلبة كلية عجلون الجامعية، وما إذا كان هذا المستوى يختلف تتعا لمتغيرات البحث المتمثلة بالجنس، (ذكر- أنثى) والتخصص الأكاديمي (علوم إنسانية، علوم تطبيقية) والحالة الاجتماعية (أعزب، متزوج)، واستخدم الباحثون أداة الدراسة التي أعدتها الغداني (٢٠١١)، وتكونت عينة الدراسة من (٦٠٠) طالب وطالبة وأشارت نتائج الدراسة إلى النتائج الآتية: - وجود فروق ذات دلالة إحصائية تبعا لمتغير الجنس وجاءت الفروق على المقياس بصورته الكلية لصالح الإناث. - وجود فروق ذات دلالة إحصائية تبعا لمتغير التخصص الأكـاديمي وجاءت الفروق على المقياس بصورته الكلية لصالح تخصص العلوم الإنسانية. -وجود فروق ذات دلالة إحصائية تبعا لمتغير الحالة الاجتماعية وجاءت الفروق على المقياس بصورته الكلية لصالح المتزوجين."
Not only does this study identifies the spiritual intelligence of the students of Ajloune university College and its relationship with some variables, but it also aims to find out whether it differs according the variable of the study namely the sex variable (male or female), the academic major (humanities or Applied Sciences).And the social status (married or single),The instrument prepared by Ghadani (2011) was adopted by the researchers for this study. The sample of the study consisted of (600) male and female students. The study showed that: - The level of the intelligence of the sample on the entire measuring instrument was average. -There were statistically significant differences according the sex variable but the differences for the entire measuring instrument were in favor of the females. - There were statistically significant differences according the academic major but the differences for the entire measuring instrument were in favor of the humanities -There were statistically significant differences according the social status but the differences for the entire measuring instrument were in favor of the married."
Keywords: طلاب الجامعات -- علم النفس الاجتماعي -- الذكاء الروحي -- التحليل النفسي